1,2,3…Testing...1,2,3… - The "Biomedically Speaking..." Podcast - Marriam Yaqoob (BioScientist: The Salford Biomedicine Society Magazine, 2024)
Mariam Yaqoob discusses her BiomedSoc project designed to engage student learning and facilitate academic networking via the ''Biomedically Speaking...'' podcast.
Keywords: biomedically speaking; podcast; academic network; collaboration; accessibility; student engagement; career advice; success support; interdisciplinary sciences; extracurricular project